(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2013)
The main purpose of this research aims to measure the role of banking strategies marketing in achieving competitive advantage within a sample of Iraqi private banks, and in order to achieve this purpose, the researcher depend on number of sober research approaches which consisted of descriptive, analytical and practical methodologies, to strengthen concepts addressed by the research, size of the sample was (56) individuals which makes up the senior leadership represented (Chairman and members of the Board of Directors, Commissioners and their assistants and department heads) while the primary tool for research (questionnaire), which has been designed based on a number of solemn scientific metrics, after adapted these metrics commensurate with the requirements of the Iraqi environment . Data that were collected through the search tool as well as the annual financial reports have been analyzed using a number of statistical tools in (SPSS.v.19) software package to get the related results. Then, the program (Excel.2010) was used to extract the financial indicators to determine the performance of banks in the sample. In the net result, the research has concluded to a number of conclusions which include: The results confirmed the presence of correlation and impact between bank marketing strategies and competitive advantage; also we found that the sample’s banks adopt a defense strategy and a high rational strategy over the strategic offensive. As most of the notable recommendations made by the current research are the necessity for bank managements to invest the positive nature of the relationship between the bank marketing strategies and competitive advantage to draw the strategic marketing direction and to build a marketing vision for top leaders.